Estimation of standby power and energy losses in South African homes - Shuma-Iwisi, Mercy Violet (My University, 2010)
In this thesis, research work on appliance standby power and energy losses is presen- ted and discussed. The research had three components: Household survey, appli- ance power consumption measurement campaign, and mathematical estimation of the standby power and energy losses. The household survey was implemented on 555 households in 11 suburbs of Greater Johannesburg in South Africa. Survey results indicate that the estimation para- meters: Appliance saturation (s) rates, appliance penetration (p) rates, time spent in standby mode (tsb) as well as appliance efficient use index (AEUI ) are clustered across the household sample. A household cluster is defined to be a group of house- holds with similar estimation parameters. Five clusters were identified in the house- hold sample. Universal appliances are identified and defined to be appliances that are common in all clusters and have saturation rates of 50% or more. Measurements were conducted in 30 households drawn from all clusters in the house- hold sample. Measurements on new appliances were done in three large appliance retail stores. Measurement results indicate wide variations in power consumption levels in appliances with same capabilities and functionalities. In some appliances, very small margins in power consumption levels exist between standby and full op- erational modes. Poor power factors are evident in most appliances in both standby and full operational modes. Consequently, relatively large components of apparent and reactive power are measured. Significant appliances are identified and defined to be appliances with the largest standby power consumption levels. Estimation was based on a mathematical model developed. The estimated standby power losses per household based on sample parameters is 73.5 W and the energy losses amount to 561.8 kWh per year. The standby power losses per household estimated using cluster parameters range from 28.2 W to 111.7 W and the respective energy losses per household per year range between 181.6 kWh to 862.1 kWh.